Cost Analysis of Monitoring Asthma Treatment using Sputum Cell Counts. Issue 7 (2008) - D'silva, Liesel; Gafni, Amiram; Thabane, Lehana; Jayaram, Lata; Hussack, Pat; Hargreave, Frederick E; Nair, Parameswaran
Abstract : BACKGROUND: In a four-centre trial, the use of sputum cell counts (sputum strategy [SS]) to guide treatment had resulted in fewer and less severe exacerbations without the need for a higher corticosteroid dose, compared with the use of symptoms and spirometry (clinical strategy [CS]). OBJECTIVE: To compare the cost of the SS with the CS in the treatment of patients with moderate to severe asthma. METHODS: In 39 patients (19 in the SS, 20 in the CS) from one of the centres, the cost (third-party payer) of the two treatment strategies was compared. Resource use data were collected using a structured questionnaire. Corresponding unit costs in 2006 Canadian dollars were obtained. RESULTS: The clinical characteristics of the patients were similar to the study population at the four centres. In the SS, the number of visits to a family physician for health disorders indirectly related to asthma (P=0.003) and the amount of inhaled long-acting beta-agonists (P=0.007) were less than that of the CS. While the total estimated median cost per patient for spirometry ($393; range $299 to $487) was less than that for sputum induction ($1, 008; range $907 to $1, 411), the total cost of the SS ($2, 265; range $1, 466 to $4, 347) was less than that of the CS ($3369; range $2208 to $3927) (P=0.216). This cost difference was due to lower costs of physician and hospital visits and services (P=0.078), of inhaled short-acting bronchodilators (P=0.067), of long-acting beta-agonists (P=0.002) and of inhaled corticosteroids (P=0.064) in the SS. CONCLUSION: In patients with moderate to severe asthma, the use of sputum cell counts to guide treatment is more effective and is likely to be less costly than management using symptoms and spirometry.